Hubungan Tingkat Pengetahuan Ibu Tentang Kanker Serviks Dengan Motivasi Ibu Melakukan Tes Pap Smear - Musdalifah, Musdalifah; Ibrahim, Ikhsan (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
Cervical cancer is cancer that occurs in the cervix uteri, and is the most common gynecological carcinoma in women. This disease originates from a viral infection that stimulates changes in the behavior of cervical epithelial cells. This research was conducted in the Working Area of the Tampa Padang Health Center, Kec. Kalukku Kab. Mamuju, used cross-sectional study method where the independent variable is the level of knowledge. While the dependent variable is Motivation. The sample size is 30 respondents. The sampling technique was purposive sampling using questionnaires which were distributed to respondents which included questions about the level of knowledge and motivation. Data analysis was carried out using the Chi-square test with a significance level of 5% (0.05). In the results of data analysis found results, (p = 0.000). The results concluded that there is a relationship between the level of knowledge about cervical cancer and the motivation of mothers to carry out pap smear test. Health workers are advised to increase campaigns to increase mothers' knowledge about pap smears.